A comparative study on false information governance in Chinese and American social media platforms. Issue 2 (31st May 2022) - Chin, Yik Chan; Park, Ahran; Li, Ke
Abstract: False information has become a profound issue of the Internet governance partly because of its serious impact on the political elections and public daily information flows. Different countries and social media platforms have adopted divergent approaches in handling false information. This study conducts a comparative study of the governance models of social media platforms in the United States and China over false Information from the perspectives of the balance of governance mechanism, that is, the balance between self‐regulation, external regulation and coregulation. It explores the laws, regulations and rules of falseinformation in two countries, exams social media platform's regulatory mechanism, focusing on comparison of Weibo and Facebook. The research shows that to increase transparency and accountability, both Weibo and Facebook have devoted certain governance power and responsibilities to internal or external intermediaries. This may induce two negative implications: accountability of the external actors and reduction of platform's supervisory obligations. The paper concludes by arguing that having a more effective, accountable and inclusive governance of false information in social media platforms, we not only need to find a balance between the functions and power of different stakeholders in governance but also need to seek a delicate balance between the three regulatory models of social media falseinformation governance.